Opinions of Academicians on Online Education: The Case of Akdeniz University Faculty of Communication in the COVID-19 Process - Gülten Adalı Aydın; Sukru Aydin (Anı Publishing, 2023)
Distance education, which has become the only option for continuing education due to the COVID-19 pandemic, has become a platform that needs to be explored and used effectively for both students and faculty members. The study aims to reveal the problems experienced in the transition to online education during the COVID-19 process and to search for solutions. Using a basic qualitative research design, the study was conducted with 10 faculty members who had experience with the online education process at Akdeniz University Faculty of Communication. The data collected through a semi-structured interview form created by the researcher were analyzed by content analysis. The study revealed that the online education process interrupted the social relations and interaction between the student and the instructor, but technically facilitated the academics' adaptation to the process by increasing their technological skills and that the academics were satisfied with the distance education platforms offered by their institutions. Academics who survived the acclimation period said they had adapted to the new system and suggested that face-to-face and online education should be implemented in a hybrid form in the future.